PROFIL POLIMORFISME GEN PROTEIN PENYANDI KAPPA KASEIN {K-KASEIN) SUSU PADA SAPI PERAH - Susmiati, Trini (2014)
Varians of K -<:asein is one of milk proteins that can be used to determine the quality of milk and can be used as effort of breeding dairy animals . K-kasein genes forms about25 %of the casein fraction of dairy milk cows . Known that there are nine alleles variant (A, B , C, E, F, G, H, I and AI ) of the K- casein gene and the involvement precentage of ale! gen K -kasein in affecting protein and milk quality produced by dairy cattle. Polymmphism (diversity) of milk gene K -<:asein produced by dairy cows , is closely related with the quality of milk protein Casein fraction of milk will affect the stability of complex colloidal particles ( micelles ) of milk. The pUIJlose of this study is to identifY the K- casein genotype and connected with the quality of milkfromdairycowsinBatuRadenKP4PurwokertoandYogyakarta. This researh will use 23 dairy cow, consists of 14 dairy cattle from KP4, and 9 dairy cattle from Batu Raden. Stages of research activities include: blood sampling for DNA extraction, DNA amplification using PCR and its products were analyzed with PCR- RFLP ( restriction enzyme Hindfi and Hind III). The results of enzyme restriction Hind I resulted three genes aile! DNA of K-<:asein from dairy milk KP4 UGM Yogyakarta and Batu Raden Purwokerto. Whereas the result from enzyme restriction Hind !II gene ale! DNAofK-<:asein found that there is no restriction from its genes. The conclutions kappa casein genes that can be digested by restriction enzymes hindf I showed polymorphism loci for DNA fragments